The Current Researches on T Follicular Helper Cells and Associated Diseases (Journal of Enam Medical College, 2012)
T follicular helper (Tfh) cell is a new subpopulation of CD4+ T cell family, whose differentiation is affected by Bcl-6, Blimp-1, STAT3, STAT5 and so on, and it could affect or decide the development of other subsets of CD4+ T cells. The important function of Tfh cell is  to help B cell mediate humoral immunity, many researches have proved that Tfh cells participate in the development of autoimmune disease, immunodeficient disease, tumor and    infectious diseases. DOI: http://dx.doi.org/10.3329/jemc.v2i2.12843 J Enam Med Col 2012; 2(2): 85-91